Global prevalence of Mycobacterium bovis infections among human tuberculosis cases: Systematic review and meta‐analysis. (24th June 2021) - Taye, Hawult; Alemu, Kassahun; Mihret, Adane; Wood, James L. N.; Shkedy, Ziv; Berg, Stefan; Aseffa, Abraham
Abstract: Tuberculosis (TB) is a chronic communicable bacterial disease caused by Mycobacterium tuberculosis complex (MTBC) species. M . tuberculosis is the main causative agent of human TB, and cattle are the primary host of Mycobacterium bovis ; due to close interaction between cattle and humans, M . bovis poses a zoonotic risk. This review summarizes and estimates the prevalence of M . bovis infection among human cases. Studies reporting TB prevalence data that were published in English during 10 years from 20 April 2009 to 17 April 2019 were identified through search of PubMed and other sources. Quality of studies and risk of bias were assessed using standard tools for prevalence study reports. Characteristics of included studies and their main findings were summarized in tables and discussed with narrative syntheses. Meta‐analysis was performed on 19 included studies, with a total of 7, 185 MTBC isolates identified; 702 (9.7%) of them were characterized as of subspecies M . bovis, but there was a large prevalence difference between the studies, ranging from 0.4% to 76.7%. The genotyping‐based studies reported significantly lower prevalence of zoonotic TB than did the studies based on older techniques. The overall pooled prevalence of M . bovis aggregated from all included studies was 12.1% of the total MTBC isolates, while the corresponding pooled figure from the 14 genotyping‐based studies was only 1.4%. Generally, human M . bovis cases reported from different countries of the world suggest that the impact of zoonotic TB is still important in all regions. However, it was difficult to understand the true picture of the disease prevalence because of methodological differences. Future investigations on zoonotic TB should carefully consider these differences when evaluating prevalence results.